2001
DOI: 10.1212/wnl.56.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of an air-circulating cooling blanket for fever control in critically ill neurologic patients

Abstract: Treatment with an air-circulating cooling blanket did not effectively reduce body temperature in febrile neuro-ICU patients treated with acetaminophen. More effective interventions are needed to maintain normothermia in patients at risk for fever-related brain damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 29 publications
0
35
0
2
Order By: Relevance
“…Approximately 4 hours were required for cooling, while the mean body temperature during the first 48 hours of hypothermia was 33.2Ϯ1°C. Interestingly, Mayer et al 13 reported significantly poorer results, with a failure rate of 42%, using a combination of cooling blankets and acetaminophen for fever control. The preliminary results of the endovascular approach evaluated in our study are thus comparable to or slightly better than those obtained by external cooling, since the time required for hypothermia induction was 3Ϯ1 hours; approximately 15 additional minutes must be calculated for catheter insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 4 hours were required for cooling, while the mean body temperature during the first 48 hours of hypothermia was 33.2Ϯ1°C. Interestingly, Mayer et al 13 reported significantly poorer results, with a failure rate of 42%, using a combination of cooling blankets and acetaminophen for fever control. The preliminary results of the endovascular approach evaluated in our study are thus comparable to or slightly better than those obtained by external cooling, since the time required for hypothermia induction was 3Ϯ1 hours; approximately 15 additional minutes must be calculated for catheter insertion.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with neurologic injury, pregnancy or the pediatric population, treatment of fevers may be beneficial [34][35][36][37][38][39]. The SCIP, and this review, focuses on perioperative warming and maintenance of normothermia, current applications of hypothermia, and the detrimental effects associated with hypothermia during the perioperative period.…”
Section: The Importance Of Maintaining Normothermiamentioning
confidence: 99%
“…In patients with neurologic injury [34,[36][37][38], who are pregnant [37], or under the age of six [34,35,39], it may be beneficial to treat or prevent hyperthermia. When controllingfever, the goal is to eliminate the cause.…”
Section: Scip Measurement and Maintenance Of Normothermiamentioning
confidence: 99%
See 2 more Smart Citations